2H-NbS2 film as a novel counter electrode for meso-structured perovskite solar cells - Feng Shao (Nature Portfolio, 2018)
Abstract We report the use of 2H-NbS2 film as a novel counter electrode in perovskite solar cells fabricated with a cold isostatic pressing method. The 2H-NbS2 film, which was prepared through an exfoliation method followed by restacking from LixNbS2 powder, shows high electrical conductivity of 8.7 × 103 S cm−1 and work function of 5.20 eV. The two-dimensional transition metal dichalcogenide was used for the first time as a counter electrode in meso-structured perovskite solar cells. Through this process, we demonstrated a new alternative to noble metals. The perovskite solar cell base on the 2H-NbS2 counter electrode showed an open-circuit voltage of 1.046 V, comparable to that of gold, and a power conversion efficiency of 8.3%.